The effects of background music tempo on consumer variety-seeking behavior: the mediating role of arousal - Sun, Wenwen; Chang, En-Chung; Xu, Yifan (Frontiers in Psychology, 2023)
Diversified purchases of consumers can help companies balance sales and inventories, which is of great significance to company profits. While existing research has explored the internal factors and external factors that influence consumers' variety-seeking behavior, little is known about the impact of background music, an important environmental cue in retail establishments, on consumer varietyseeking behavior. The present research investigates the influence of background music tempo on consumer variety-seeking behavior, along with its underlying mechanism and boundary condition. Five experiments revealed that background music tempo affects consumers' variety-seeking behavior (Study 1a, 1b & 4). Specifically, fast-tempo background music increases consumers' variety-seeking behavior (Study 1b). Arousal mediates the main effect (Study 2), as fast-tempo background music increases consumers' variety-seeking behavior by enhancing consumers' arousal. Moreover, participants' familiarity with the background music moderates the impact of background music tempo on consumer variety-seeking behavior (Study 3). Only when consumers have a high degree of familiarity with the background music they listen to, the tempo of the background music will have a significant impact on their variety-seeking behavior.